Luiz Beltrão, Décio Pignatari, Muniz Sodré and Sérgio Capparelli. Brazilian Theoretical Contributions to Latin American Thought in Communication - León Duarte, Gustavo A. (Mediaciones Sociales, 2011)
The paper centers on defining some structural characteristics that identify four emblematic researchers of the Sciences of the Communication in Brazil: Luiz Beltrão, Décio Pignatari, Muniz Sodré and Sérgio Capparelli. The paper attempts to define why these Brazilian theoretical contributions to establish a communication thought in itself in communication studies in Brazil and Latin America in general. The closure that identifies the Brazilian specialists analyzed here is the ethical-political platform of communication, amalgamated with a multidisciplinary approach, and a socio-historical criticism of its subjects, objects and methods of study.
Keywords: communication research; ethics; epistemology; Latin America